Does intra‐operative flexible endoscopy reduce anastomotic complications following left‐sided colonic resections? A systematic review and meta‐analysis. (17th July 2019) - Aly, M.; O'Brien, J. W.; Clark, F.; Kapur, S.; Stearns, A. T.; Shaikh, I.
Abstract: Aim: Postoperative anastomotic leakage (AL) or bleeding (AB) significantly impacts on patient outcome following colorectal resection. To minimize such complications, surgeons can utilize different techniques perioperatively to assess anastomotic integrity. We aim to assess published anastomotic complication rates following left‐sided colonic resection, comparing the use of intra‐operative flexible endoscopy (FE) against conventional tests used to assess anastomotic integrity. Methods: PubMed/MEDLINE and Embase online databases were searched for non‐randomized and randomized case–control studies that investigated postoperative AL and/or AB rates in left‐sided colonic resections, comparing intra‐operative FE against conventional tests. Data from eligible studies were pooled, and a meta‐analysis using Review Manager 5.3 software was performed to assess for differences in AL and AB rates. Results: Data from six studies were analysed to assess the impact of FE on postoperative AL and AB rates (1084 and 751 patients respectively). Use of FE was associated with reduced postoperative AL and AB rates, from 6.9% to 3.5% and 5.8% to 2.4% respectively. Odds ratios favoured intra‐operative FE: 0.37 (95% CI 0.21–0.68, P = 0.001) for AL and 0.35 (95% CI 0.15–0.82, P = 0.02) for AB. Conclusion: This meta‐analysis showed that the use of intra‐operative FE is associated with a reduced rate of postoperative AL and AB, compared to conventional anastomotic testing methods.